Extrapulmonary small cell carcinoma: Current status and strategy - Rouniyar, B P; Devkota, K R (Journal of Chitwan Medical College, 2017)
Extrapulmonary small cell carcinoma is very rare. Its prognosis is poor and there is no established treatment modality. It has been considered as a distinct clinicopathological entity. It is distinct from small cell carcinoma of the lung, though it shares similar clinicopathologic features to the latter. It has a similar staging and treatment modality. The aim is to review existing studies and provide new results on diagnosis and current management strategy for patients with extrapulmonary small cell carcinoma. The study involves the review of the literature using the electronic database MEDLINE and hand searching of journals. The outcome measures are addressed and analyzed. Studies have shown wide variations of treatment modalities adopted and the outcome observed. Almost all studies are of inadequate power to establish standard treatment modality. Multi-centre studies are required to institutionalize standard treatment modality.